A nonconjugated radical polymer with stable red luminescence in the solid state. Issue 10 (26th July 2022) - Wang, Zhaoyu; Zou, Xinhui; Xie, Yi; Zhang, Haoke; Hu, Lianrui; Chan, Christopher C. S.; Zhang, Ruoyao; Guo, Jing; Kwok, Ryan T. K.; Lam, Jacky W. Y.; Williams, Ian D.; Zeng, Zebing; et al.
Abstract : A radical polymer without any delocalized π-stabilization was synthesized from a classical chromophore quencher, TEMPO, which surprisingly shows red emission. Abstract : Organic radicals are unstable and stable radicals usually display non-luminescent properties. Luminescent radicals possess the all-in-one properties of optoelectronics, electronics, and magnetics. To date, the reported structures of luminescent radicals are limited to triphenylmethyl radical derivatives and their analogues, which are stabilized with extended π-conjugation. Here, we demonstrate the first example of a nonconjugated luminescent radical. In spite of the lack of delocalized π-stabilization, the radical polymer readily emits red luminescence in the solid state. A traditional luminescent quencher, 2, 2, 6, 6-tetramethylpiperidin-1-yl turned into a red chromophore when grafted onto a polymer backbone. Experimental data confirm that the emission is associated with the nitroxide radicals and is also affected by the packing of the polymer. This work discloses a novel class of luminescent radicals and a distinctive pathway for luminescence from open-shell materials.